Neural correlates of electrointestinography: Insular activity modulated by signals recorded from the abdominal surface. (19th March 2015) - Hashimoto, T.; Kitajo, K.; Kajihara, T.; Ueno, K.; Suzuki, C.; Asamizuya, T.; Iriki, A.
Highlights: Resting-state intestinal activity was recorded from the abdominal surface. Concurrent fMRI design revealed neural correlates of intestinal activity. Right insula activity was correlated with signals from the abdominal surface. Cortical intestinal network of insula–ACC was modulated by anxiety scores. Abstract: Although the neural correlates that underlie abdominal pain have been investigated, so-called brain processes involved in modulating "gut feelings" remain unclear. In the current study, we used electrointestinography (EIG) to measure intestinal activity of healthy humans at rest. EIG measured myoelectrical activity of intestinal smooth muscles from the abdominal surface and was simultaneously conducted along with brain activity measurement using functional magnetic resonance imaging (fMRI). Correlations between the frequency powers of EIG and fMRI signals during 30 min of rest were then examined to elucidate gut–brain interactions. Neural activity correlating with 0.14- to 0.21-Hz EIG (suggested to reflect intestinal activity) was observed in the right anterior and middle insula. Moreover, this EIG frequency band correlated with anxiety scores along with resting-state functional connectivity between the insula and dorsal anterior cingulate cortex. These findings suggest that the insular cortex could be the core region involved in central visceral processes associated with subjective feelings.